Integrasi Kearifan Lokal dan Literasi Digital dalam Pembelajaran Pendidikan Agama Islam Berbasis Karakter di Era Abad ke-21 - Abd Rohim; Ahmad Faiz; Adim Jaya Sumba; M Mahbubi (Qudwah: Journal of Islamic Education, 2025)
Islamic Religious Education (PAI) in Indonesia faces significant challenges in the 21st century, primarily due to globalization, digitalization, and increasingly complex socio-cultural dynamics. These conditions require PAI learning to be oriented not only toward mastering religious knowledge but also toward strengthening digital literacy and internalizing local wisdom to shape inclusive and tolerant student character. This study aims to identify models for integrating local wisdom and digital literacy into PAI materials and to identify supporting and inhibiting factors for their implementation in contemporary learning contexts. This research employed a qualitative approach through literature review, analysis of PAI curriculum documents, and semi-structured interviews. Interviews were conducted with eight informants: five junior high and senior high school PAI teachers and three Islamic education practitioners from three regions with diverse cultural backgrounds. Data were analyzed using data reduction, categorization, and thematic conclusion drawing. The results revealed three key findings. First, the integration of local wisdom into Islamic Religious Education (PAI) is most effective when values ​​such as tolerance, mutual cooperation, and respect for diversity are directly contextualized within the material on faith, morals, and Islamic jurisprudence through digital-based local case studies. Second, the use of interactive digital media—such as narrative videos based on local culture, online learning platforms, and educational apps—significantly increases student engagement and strengthens the understanding of moderate Islamic values. Third, the success of integration is strongly influenced by teachers' digital literacy competencies and the policy support of educational institutions.However, this study also identified major obstacles in the form of limited teacher digital competencies, disparities in technological infrastructure, and resistance on the part of some educators to changes in traditional learning paradigms. The study's conclusions emphasize the need to develop contextual Islamic Religious Education (PAI) learning models based on local wisdom and digital literacy, accompanied by teacher training policies and the provision of sustainable digital resources to ensure PAI remains relevant and responsive to the challenges of the 21st century.